Innate scavenger receptor-A regulates adaptive T helper cell responses to pathogen infection - Zhipeng Xu (Nature Portfolio, 2017)
Scavenger receptors can function as pattern recognition receptors to sense infection. Here the authors show that, in response to worm and bacterial infection, scavenger receptor class A prevents nuclear localization of IRF5 and thereby drives M2 polarization and associated type 2 immune responses.